A new species of the solifuge genus Galeodes Olivier, 1791 from southeastern Turkey (Solifugae, Galeodidae) - Erdek, Melek (Zootaxa, 2021)
The family Galeodidae Sundevall, 1833 is the most speciose family of order Solifugae. A new galeodid, Galeodes hakkariensis sp. n., is described and illustrated on the basis of both sexes from Hakkari Province in Turkey. The flagellum, flagellar complex setae, setal arrangements on the tarsi and metatarsi of pedipalps and walking legs, shape and number of the stridulatory setae, dentition, and the other characteristics are described and illustrated in details. With this description, the number of known species of Galeodes Olivier, 1791 is raised to 174.